MOTIVASI SEBAGAI MEDIASI PENGARUH PELATIHAN DAN DISIPLIN TERHADAP KINERJA KARYAWAN - Mulyadi, Made; Galung Indra Kiswara, Putu; Gede Elvina Adi Saputri, Luh; Wirati Adriati, IGA (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Training is a short educational process that uses structured and organized methods, where non-managerial employees acquire technical knowledge and skills within certain limits. Training has a significant impact on improving employee capabilities, providing motivation, and building self-confidence, so that it can improve their performance. This study aims to evaluate the role of job training and work discipline on employee performance, with work motivation as a mediator at PT. Secana Beachtown. The number of samples used was 82 employees. This study uses a quantitative method. Data analysis techniques used include validity testing, reliability testing, descriptive analysis, SEM Partial Least Square, and VAF (Variance Accepted For) for mediation testing. This study found that job training, discipline, and work motivation have a positive effect on employee performance at PT. Secana Beachtown, with work motivation as a mediating variable.